Book Review: Landscape, by John Wylie - Kunz, Jaciel Gustavo (Geografares, 2019)
Book Review: Landscape, by John WylieThis book is part of the Key Ideas in Geography series, by British publisher Routledge. According to Routledge, the series offers accessible but complete texts about key concepts of space, focusing not only on Geography, but also on the Humanities and Social Sciences in general. About the concept of landscape, the approach by Humanist-Cultural Geography was achieved by the work of the young professor John Wylie, of Irish origin.Landscape is the only complete book published by him to date; therefore, it is one of his main publications. Although published a few years ago, the work is still up-to-date in the treatment of current of thoughts and other themes related to the concept of landscape. Much cited abroad, the book has not been much disseminated in Brazil so far. This book review proposes to invite brazilians scholars to know more about the author and his work and to consider including it in their personal or institutional collections, as well as in their references.